A Sustainable Islamic Microfinance Model in the True Spirit of Islam - Dr. Talat Hussain; Muhammad Nadeem Khalil Ali (Islamic Banking and Finance Review, 2017)
Microfinance is considered an effective tool in alleviating poverty all over the world. The objective of this paper is to develop a sustainable Islamic Microfinance model in the true spirit of Islam. Despite its importance, the microfinance sector accounts less than 1% of the overall Islamic Finance industry although 1.2 billion of global population is living below poverty line (earning less than $2 per day) and 44% of which are living in Muslim countries. Similarly the current practices of Islamic Banks and Islamic Microfinance Institutions are based on the principles of materialism rather than the concept of falah (success in this worldly life and hereafter) due to which they havefailed to achieve the objective of fair distribution of wealth in the society and alleviating poverty from the society. Therefore, in this paper an Islamic Microfinance Model based on the moral and ethical values of Islam (Piety, Justice, Benevolence, Cooperation, equality, selflessness avoidance from materialism) is developed. This model proposes Musharakha, Modarabah, Wakalah and Qarz-e-Hasana as the ideal modes of Islamic Microfinance because legitimacy of these modes of financing is beyond any doubt. In this Islamic Microfinance Model various steps are proposed for microfinance institutions, central bank and government. If this model is implemented in true letterand spirit, it can result in balanced growth and bring harmony in the various segments of the society by reducing poverty, increasing employment and fair distribution of wealth among them and thus contribute in the economic development and social wellbeing of the people.